The Influence of Indonesian Language Literacy and Self-Confidence on the Sales Communication Skills of Students in the Retail Business and Management Program - Novita Wulandari; Adi Nurhadi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the influence of Indonesian language literacy and self-confidence on the sales communication skills of students in the Retail Business and Management Program. The primary issue addressed is the importance of strengthening the sales communication competencies of vocational students, which are determined not only by language proficiency but also by the psychological factor of self-confidence. This study employed a quantitative approach using a correlational-predictive research design. The sample consisted of 100 students enrolled in the Retail Business and Management Program. Data were collected through an Indonesian language literacy test, a self-confidence questionnaire, and a sales communication skills assessment instrument. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression with the assistance of statistical software. The findings indicate that the students' Indonesian language literacy was categorized as high, with a mean score of 78.64, while the mean scores for self-confidence and sales communication skills were 80.12 and 81.36, respectively. The correlation analysis revealed that Indonesian language literacy was positively and significantly associated with sales communication skills (r = 0.621), whereas self-confidence also demonstrated a positive and significant relationship with sales communication skills (r = 0.688). The multiple regression analysis showed that Indonesian language literacy and self-confidence simultaneously exerted a significant influence on sales communication skills (F = 70.12, p < 0.001, R² = 0.591). Partially, self-confidence emerged as the most dominant predictor, with a standardized beta coefficient of 0.519. This study concludes that strengthening Indonesian language literacy and self-confidence is essential for improving the sales communication skills of students in retail vocational education.